2010
DOI: 10.1111/j.1600-079x.2009.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic melatonin treatment and its precursor L-tryptophan improve the monoaminergic neurotransmission and related behavior in the aged rat brain

Abstract: Melatonin has an important role in the aging process as a potential drug to relieve oxidative damage, a likely cause of age-associated brain dysfunction. As age advances, the nocturnal production of melatonin decreases potentially causing physiological alterations. The present experiments were performed to study in vivo the effects of exogenously administered melatonin chronically on monoaminergic central neurotransmitters serotonin (5-HT), dopamine (DA) and norepinephrine (NE) and behavioral tests in old rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 57 publications
3
36
0
1
Order By: Relevance
“…This is mainly because of the fact that it decreased both the number of bursts and the firing rate of VTA-DA neurons. The involvement of melatonin in the control of DA transmission is in line with data showing that a chronic treatment with melatonin alone induces an increase in the tissular level of DA in old rats (Esteban et al, 2010). Further experiments are necessary to determine whether melatonin by itself can induce a modification of the discharge pattern of VTA-DA neurons.…”
Section: Effects Of Agomelatine On Monoaminergic Systemssupporting
confidence: 75%
“…This is mainly because of the fact that it decreased both the number of bursts and the firing rate of VTA-DA neurons. The involvement of melatonin in the control of DA transmission is in line with data showing that a chronic treatment with melatonin alone induces an increase in the tissular level of DA in old rats (Esteban et al, 2010). Further experiments are necessary to determine whether melatonin by itself can induce a modification of the discharge pattern of VTA-DA neurons.…”
Section: Effects Of Agomelatine On Monoaminergic Systemssupporting
confidence: 75%
“…It is well known that antioxidants are potent scavengers of free oxygen radicals and serve as inhibitors of oxidative stress [1]. Melatonin (Mel), a multifunctional indolamine, is released from the pineal gland [20]. Recent studies revealed that Mel and its receptors are present in the pancreas, whereas its production is independent from the pineal gland [41].…”
mentioning
confidence: 99%
“…This has been amply documented in studies where melatonin was shown to protect against tissue damage and cellular death resulting from free radicals generated as a result of processes that either involve exposure to radioactivity or other toxins that stimulate free radical production. Thus, melatonin has been repeatedly shown to reduce free radical-mediated damage in the gastrointestinal tract [87], lungs [68], liver [69,88], kidney [89], testis [54], urinary bladder [90], pancreas [91], bone marrow [92], brain [38,93] and spinal cord [20], skeletal muscle [19], and other organs as well. These ubiquitous actions of melatonin show that its distribution in the body is not limited to only some organs.…”
Section: Melatonin As a Radioprotector: In Vivo Studiesmentioning
confidence: 98%